DAMPAK KEKUATAN GENGGAMAN TANGAN DAN KOORDINASI PADA KETERAMPILAN PUKULAN DRIVE MELALUI MOTIVASI DALAM PERMAINAN BULUTANGKIS - Donie Donie (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
To identify causal factors that are directly and indirectly related to athlete's drive skills, it is necessary to know the effect of handgrip strength, coordination, and motivation. This study involved 45 athletes to test causative variables related to drive skills. All participants underwent several tests consisting of handgrip strength test (using grip dynamometer), ball catching coordination, and motivation (through questionnaire), as well as drive skill through Badminton Wall Volley Test. The data were analyzed through Path analysis using IBM SPSS software (p <0.05) to see the causal relationship of independent and dependent proposed variable.The strength of handgrip significantly had a positive direct effect on coordination (p <0.05) or H0 was rejected. Meanwhile, it did not directly influence motivation (p> 0.05) or H0 is accepted. Coordination also did not have direct effect on motivation (p> 0.05) or H0 is accepted. Handgrip strength significantly and positively influenced drive skills (p <0.05) or H0 is rejected. Coordination had significant and positive direct effect on drive skills (p <0.05) or H0 is rejected. Motivation had no direct effect on drive skills (p> 0.05) or H0 is received. The study shows that there is a causal relationship between the strength of hand grip and coordination toward drive skill. Furthermore, greater coordination also influenced drive skill since coordination is one's ability to receive stimuli quickly to make decisions about something that is seen.